Magnitude and predictors of undernutrition among children aged six to fifty nine months in Ethiopia: a cross sectional study - Hiwot Darsene; Ayele Geleto; Abebaw Gebeyehu; Solomon Meseret (BMC, 2017)
Abstract Background Undernutrition among children continues to be a major public health problem in developing countries. In Ethiopian, 44% of under-five children were stunted while 29% and 10% were underweight and wasted respectively. However, predictors of undernutrition among children were not clearly known in the study area. Therefore, this study was aimed at determining prevalence and predictors of undernutrition among children aged 6-59 months in Hawassa town. Method A community based cross-sectional study was conducted among 811 randomly selected children paired with their mothers/caregivers. Mothers/caregivers were interviewed to obtain social-demographic data and feeding practice. Anthropometric measurement was conducted to obtain anthropometric data. Data were entered into EPI info 6.04 and exported to SPSS 16 for analysis. Bivariate logistic regression analysis with Crude Odds Ratio at 95%CI was used to assess presence of association among variables. Multivariate logistic regression analysis with Adjusted Odds Ratio at 95%CI was conducted to determine predictors of undernutrition and association was declared significant at p ≤ 0.05. Result The result of our study indicated that 39.3%, 15.8% and 6.3% of children were stunted, underweighted and wasted respectively. Multivariate logistic regression analysis identified male sex, mother older than 35 years, not fed on colostrum, cessation of breastfeeding before two years of age, frequency of complementary feeding per day and diarrheal morbidity in the last 12 months were statistically associated with stunting. Maternal education, family sizes and diarrheal morbidity in the past 12 months were significantly associated with underweight. Similarly, frequency of complementary feeding per day, age at cessation of breastfeeding, preceding birth interval and not fed on colostrum were associated to wasting. Conclusion The prevalence of undernutrition; stunting, underweight and wasting, among under-five children is very common in the study area. Inappropriate feeding practice and diarrheal morbidity were found to be the main risk factors for undernutrition. Appropriate factor specific interventions including counseling on optimal child feeding practice and diarrhea prevention should be strengthened in the study area.